Definition of a urgency of conducting a healthy way of life by students. - Kipko G.O (Kharkov National Pedagogical University, 2010)
The attitude and knowledge of students about unhealthy habits is considered. 90 students took part in research. Factors which induce are resulted or prevent conducting a healthy way of life. Levels of a self-estimation of a state of health of students are shown. The resulted factors of influence on a state of health of an environment, physical, medical and hygienic activity of students. It is established what to conduct a healthy way of life to students a poor-quality feed, environmental contamination, educational overloads interfere infringement of a daily mode of dream.